1995
DOI: 10.1103/physrevc.51.2739
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic nuclear structure effects in quasielastic neutrino scattering

Abstract: Charged-current cross sections are calculated for quasielastic neutrino and antineutrino scattering using a relativistic meson-nucleon model. We examine how nuclear-structure effects, such as relativistic random-phaseapproximation (RPA) corrections and momentum-dependent nucleon selfenergies, influence the extraction of the axial form factor of the nucleon. RPA corrections are important only at low-momentum transfers. In contrast, the momentum dependence of the relativistic self-energies changes appreciably th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 26 publications
2
75
0
1
Order By: Relevance
“…In presented calculations only density dependent part of the polarization tensors is taken into account [12]. Contributions from the divergent Feynman parts are omitted.…”
Section: Model Of the Nucleusmentioning
confidence: 99%
See 3 more Smart Citations
“…In presented calculations only density dependent part of the polarization tensors is taken into account [12]. Contributions from the divergent Feynman parts are omitted.…”
Section: Model Of the Nucleusmentioning
confidence: 99%
“…Following H. Kim et al [12] a short-range correlation effect is taken into account by introducing the LandauMigdal parameter (g ′ = 0.7) into the pion propagator. Using the interaction introduced above the ring random phase approximation is performed [19].…”
Section: Model Of the Nucleusmentioning
confidence: 99%
See 2 more Smart Citations
“…While early calculations only were taking into account the nucleon mass reduction in the medium, important progress has been realized since then in order to include Hartree-Fock [10], random phase approximation (RPA) [11,12,13,14,15,16,17] or ladder [18,19,20,21,22,23,24] correlations. It is generally found that the neutrino opacities are suppressed by medium effects, if however no collective mode is excited [16].…”
Section: Introductionmentioning
confidence: 99%